2016
DOI: 10.1039/c5nr06948c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of antireflective silica coatings through the synergy of polypeptide layer-by-layer assemblies and biomineralization

Abstract: We report a versatile approach to synthesize silica coatings with antireflective (AR) characteristics through the combination of a layer-by-layer (LbL) assembly technique and biomineralization. LbL assembled decanoyl-modified poly(l-lysine)/poly(l-glutamic acid) (PLL-g-Dec/PLGA) multilayer films were used as templates for silica mineralization, followed by calcination. The specific deposition of silica onto the LbL polypeptide assemblies through amine-catalyzed polycondensation resulted in silica coatings that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Unlike the conventional polymer multilayers with a characteristic growth rate of 2–4 nm per bilayer, the CNF multilayers showed a much lower increment of 1–1.5 nm per layer (Figure S3, Supporting Information). [ 37–39 ] As shown in Figure 2c, after 3 cycles of PL/CNF 5 assembly, the resultant LC3 films achieved a thickness of 29 nm without disassembly, confirming the strong hydrogen bonding of CNF networks and physical bonding (i.e., electrostatic interaction and molecular entanglement) of PL layers. [ 40 ] The surface roughness of these coatings varied due to their different components and structures (Figure 2d).…”
Section: Resultsmentioning
confidence: 82%
“…Unlike the conventional polymer multilayers with a characteristic growth rate of 2–4 nm per bilayer, the CNF multilayers showed a much lower increment of 1–1.5 nm per layer (Figure S3, Supporting Information). [ 37–39 ] As shown in Figure 2c, after 3 cycles of PL/CNF 5 assembly, the resultant LC3 films achieved a thickness of 29 nm without disassembly, confirming the strong hydrogen bonding of CNF networks and physical bonding (i.e., electrostatic interaction and molecular entanglement) of PL layers. [ 40 ] The surface roughness of these coatings varied due to their different components and structures (Figure 2d).…”
Section: Resultsmentioning
confidence: 82%
“…Recently, our group has demonstrated that nanostructured materials with tunable porosity and thickness can be fabricated using the synergy between the LbL assembly technique and biomimetic mineralization. Biomimetic mineralization occurred in the biological systems and leads to complex structures and morphology spanning from nano- to microscale mediated by proteins or peptides via self-assembly and template processes. Inspired by these biological systems, many studies have demonstrated the biomimetic synthesis of inorganic materials with a variety of morphologies by mineralization of self-assembled templates such as vesicles, micelles, nanofibers, and nanotapes. Meanwhile, their nanostructures were dictated by polypeptide chain conformations such as α-helix and β-sheet adopted by polypeptides. With the combined advantages of biomineralization and LbL assembly technique, it is promising to prepare mesoporous silica coatings templated by polypeptide LbL assemblies with tunable AR characteristics by varying the percentage of hydrophobic domain, polypeptide molecular weight (MW), and number of deposition layer . In addition, biomineralization can warrant the deposition of continuous and intact inorganic domain in the polymeric network.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, our previously reported porous silica coatings onto glass substrate templated by alkyl chain-modified PLL/PGA LbL assembled films showed the deterioration of their AR performance over time upon placing at ambient environment, whereas their AR performance can be resumed by removing the water that resided in the films via heating treatment (60 °C). 25 On the basis of the results, it is highly possible that the silica/(PDMA-b-PTFP/PLGA) com-posite films exhibited the patchy surface comprised of silica and low-surface energy PTFP both on the surface of the pores, which would consequently prevent water molecules from infiltrating into the porous films. The coated substrates exhibited low water contact angles, suggesting that the composite film was covered with more siliceous materials on the surface than inside the films.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 96%
“…Solution-based processes including sol-to-gel process and layer-by-layer (LbL) assembly are relatively easy and cost-effective as compared to other processes. The fabrication of ARCs via LbL assembly has been shown to be feasible, and an average transmittance about 97.0% or above at the visible wavelength range (400–800 nm) on substrates can be achieved, , whereas many of the approaches required high temperature treatment, which can be only restricted to inorganic substrates. Polymeric substrates such as poly­(methyl methacrylate) (PMMA) and polyethylene terephthalate (PET) exhibited low heat resistance and low adhesion of inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation